Geodiversity assessment of Shkodra Municipality, Albania - Kraja, Drisela; Albert, Gáspár (Quaestiones Geographicae, 2025)
The objective of this paper is to present a quantitative assessment of geodiversity for Shkodra Municipality, which is located in north-western Albania and comprises an area of 953.64 km2. It is one of the richest geosites in Albania, with Lake Shkodra being the largest lake in the Balkan Peninsula, situated along the Adriatic Sea shore and extending up to the Albanian Alps. The municipality’s favourable geographical positioning and climatic conditions offer numerous benefits for expanding diverse forms of tourism, particularly geotourism activities, which allow visitors to engage with the peculiar geological features of the municipality. The cultural heritage of the municipality, with the ancient Rozafa Castle at its heart, is a key factor in its appeal as a tourist destination. This assessment represents the first research that demonstrates the complex diversity of the geoscientific features of Shkodra Municipality. Geodiversity was calculated based on the geological, palaeontological, soil, mineral occurrences, and morphological diversity of the area using published maps and geodatabases. It was found that two-thirds of the municipality is classified as medium or high geodiversity, and 10% as very high geodiversity. Four main hotspots of very high geodiversity were identified, allowing a concentrated presentation of the geological heritage and enhancing visitors’ understanding of the area. Shkodra’s geodiversity is vital for promoting geotourism and for reflecting the cultural and historical background of the municipality. This study also contributes to the knowledge of the geological and geomorphological features and promotes geoconservation.